SOME CHANGES IN THE PSYCHOMOTORISM OF STUDENTS WITH DIFFERENT LEVELS IN MOTOR ACTIVITY - L. Kasabova (Trakia Journal of Sciences)
Hypodynamia and hypokinesia are the main cause of decreased motor activity among students, resulting in lower vital parameters, deterioration in health and lowering the learning abilities. The quality of the physical education process in the higher school levels depends to a large extent on the psychological processes of the trainees. In the study we aim to identify some features of psycho-motor characteristics and to compare the level of learning of the total study material in students with different levels of motor activity. The following methods that were used: analysis of literary sources, sports-pedagogical experiment, sports-pedagogical testing, and mathematical-statistical analysis. Sixty (60) UNWE students were divided into two groups. The first one includes those who regularly participate in sport classes and the second one is formed by students not regularly attending those activities. The results of the study show that regular sports activities have a positive impact on the concentration of thought processes. Improvements in the psycho-motor of motor activity in students, lead to an increase in their activity during the educational and work process. We encourage students to attend regular physical education classes and practice sports in their spare time.